2014
DOI: 10.1080/10810730.2014.941519
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement to Enhance Child Survival and Early Development in Low- and Middle-Income Countries: An Evidence Review

Abstract: As part of a broader evidence summit, USAID and UNICEF convened a literature review of effective means to empower communities to achieve behavioral and social changes to accelerate reductions in under-5 mortality and optimize early child development. The authors conducted a systematic review of the effectiveness of community mobilization and participation that led to behavioral change and one or more of the following: child health, survival, and development. The level and nature of community engagement was cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 39 publications
1
103
0
Order By: Relevance
“…This corresponds to a previous review which found that community sensitization around seeking timely and appropriate treatment led caregivers to favour CHWs over traditional healers as first point of care [43]. These findings confirm that such participatory approaches can improve dialogue and action-oriented decision-making and increase participation by communities, families and individuals, which can result in increased demand for health services and information seeking/sharing and positive changes in individual behaviours and social norms and practices [18]. A recently published study demonstrated that a community dialogue intervention was effective at producing changes in underlying social and cultural factors related to HIV in Mozambique, including gender norms and roles, stigma, knowledge and some behaviours [33].…”
Section: Discussionsupporting
confidence: 87%
“…This corresponds to a previous review which found that community sensitization around seeking timely and appropriate treatment led caregivers to favour CHWs over traditional healers as first point of care [43]. These findings confirm that such participatory approaches can improve dialogue and action-oriented decision-making and increase participation by communities, families and individuals, which can result in increased demand for health services and information seeking/sharing and positive changes in individual behaviours and social norms and practices [18]. A recently published study demonstrated that a community dialogue intervention was effective at producing changes in underlying social and cultural factors related to HIV in Mozambique, including gender norms and roles, stigma, knowledge and some behaviours [33].…”
Section: Discussionsupporting
confidence: 87%
“…They need to be complemented with interventions targeting communities and health care systems (Elder, 2001; Pequegnat, 2011). Other articles in this issue of the journal focus on these other levels of analysis (Farnsworth et al, 2014; Vélez et al, 2014). …”
Section: Role Of Parents/caregiversmentioning
confidence: 99%
“…Ultimately, the purpose is to facilitate ways for young children to contribute to their own communities. There is evidence that 'programs working collaboratively or achieving shared leadership with a community can lead to behaviour change and cost-effective sustained transformation to improve critical health behaviours and reduce poor health outcomes in low-and middle-income countries' (p. 68) yet children are more often than not considered as part of the desired target group or outcome rather than key actors in effective community mobilisation and participation (Farnsworth et al, 2014).…”
Section: Discussionmentioning
confidence: 99%